Effects of fish cage culture and suspended oyster culture on macrobenthic communities in Xiangshan Bay, a semi-enclosed subtropical bay in eastern China. (May 2019) - Liao, Yibo; Shou, Lu; Jiang, Zhibing; Tang, Yanbin; Du, Ping; Zeng, Jiangning; Chen, Quanzhen; Yan, Xiaojun; Chen, Jianfang
Abstract: The impacts of fish cage culture and suspended oyster culture on macrobenthic communities were investigated in Xiangshan Bay, China, on a seasonal basis from January to October of 2015. Samples were collected from a fish cage farm, a suspended oyster farm, and two corresponding reference sites. Two-way ANOVA results showed that species richness, abundance, biomass, and Shannon–Wiener diversity differed significantly between the four different investigated areas, and different seasons as well. Cluster analysis showed that macrobenthic community composition in the fish and oyster culture areas significantly differed from that in the reference sites, respectively. Trophic structure of macrobenthos in the fish and oyster culture areas mostly clustered together owing to higher abundance and biomass of surface-deposit feeders and carnivores. The macrobenthic communities and feeding guilds correlated highly with environmental factors, such as bottom water chlorophyll a and nutrients, as well as sediment total organic carbon. Although integrated multi-trophic aquaculture is regarded as a suitable approach to coordinate desirable economic, social, and environmentally sustainable outcomes, coastal ecosystems may suffer from large-scale nutrient enrichment due to aquaculture and other human activities, which should not be considered in isolation. Highlights: Benthic impacts of fish cage culture and suspended oyster culture were compared. Macrobenthic community in fish farm differed significantly from the other sites. Surface deposit feeders and carnivores benefited from benthic organic enrichment. Macrobenthic communities and feeding guilds correlated with environmental factors.